Scanning Tunneling Spectroscopy on InAs–GaSb Esaki Diode Nanowire Devices during Operation - Persson, Olof (Nano Lett, 2015)
[Image: see text] Using a scanning tunneling and atomic force microscope combined with in-vacuum atomic hydrogen cleaning we demonstrate stable scanning tunneling spectroscopy (STS) with nanoscale resolution on electrically active nanowire devices in the common lateral configuration. We use this method to map out the surface density of states on both the GaSb and InAs segments of GaSb–InAs Esaki diodes as well as the transition region between the two segments. Generally the surface shows small bandgaps centered around the Fermi level, which is attributed to a thin multielement surface layer, except in the diode transition region where we observe a sudden broadening of the bandgap. By applying a bias to the nanowire we find that the STS spectra shift according to the local nanoscale potential drop inside the wire. Importantly, this shows that we have a nanoscale probe with which we can infer both surface electronic structure and the local potential inside the nanowire and we can connect this information directly to the performance of the imaged device.